2020
DOI: 10.1186/s12935-020-1097-2
|View full text |Cite
|
Sign up to set email alerts
|

CircZDHHC20 represses the proliferation, migration and invasion in trophoblast cells by miR-144/GRHL2 axis

Abstract: Background: Preeclampsia (PE) is a prevalent pregnancy disorder that has been one of the leading causes of maternal and perinatal mortality worldwide. Circular RNAs (circRNAs) have recently considered as important regulators in PE pathogenesis. In the current study, we aimed to explore the impact and mechanisms of circRNA zinc finger DHHCtype palmitoyltransferase 20 (circZDHHC20) in PE pathogenesis. Methods: RNase R assay and reverse transcription with Oligo(dT) 18 primers were performed to confirm that circ-Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 27 publications
4
20
0
Order By: Relevance
“…Reportedly, PE has a long-term impact on cardiovascular disease development [ 26 ]; hence, early detection and intervention are particularly important. Recently, increasing evidence has suggested that circRNA is associated with PE [ 27 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, PE has a long-term impact on cardiovascular disease development [ 26 ]; hence, early detection and intervention are particularly important. Recently, increasing evidence has suggested that circRNA is associated with PE [ 27 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…24 h later, the cells passing through the membrane were fixed with paraformaldehyde and stained with 0.1% crystal violet (Cat#C0121, Beyotime). Then the crystal violet-stained cells were imaged and counted (magnification 200 ×) [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…The plates were washed with 1 mL of fresh growth medium to remove the suspended cells and then cultured in the incubator at 37 °C. Images were captured at 0 and 24 h and wound widths were quantitatively examined using a standard caliper [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher expression of lncRNA PSG10P contributed to PE pathogenesis by regulating miR-19a-3p and IL1RAP (Wang et al, 2019). CircTRNC18 and circZDHHC20 sponge miR-762 and miR-144, respectively, affect the expression of GRHL2 and repress migration of trophoblast cells (Shen et al, 2019;Zhou et al, 2020). Due to their unique circular structure, circRNAs are resistant to ribonucleases and are more stable in body fluids or exosomes than linear RNAs.…”
mentioning
confidence: 99%